[PP.07.14] RENAL DOPAMINERGIC SYSTEM DYSFUNCTION ASSOCIATED TO HIGH BLOOD PRESSURE AND INFLAMMATION IN FRUCTOSE OVERLOAD INDUCED METABOLIC SYNDROME. (September 2017) - Puyó, A.; Mikusic, N. Rukavina; Kouyoumdzian, N.; Robbesaul, G.; Primo, M. Alvarez; Lee, H.; Toblli, J.; Fernández, B.; Choi, M.
Abstract : Objective: The renal dopaminergic system (RDS) promotes sodium excretion and anti-inflammatory actions. Fructose overload (FO) produces in the rat hemodynamic and metabolic changes similar to the human metabolic syndrome. These changes are associated to an impairment of the RDS, leading to renal inflammation, sodium retention and blood pressure elevation. The aim of this study was to evaluate RDS state and its relation to hypertension and overexpression of renal inflammatory markers in the FO experimental model. Design and method: Six groups of male Sprague Dawley rats (six weeks at the beginning of the treatment) were studied: Control (C4, C8 and C12, tap water to drink) or FO (F4, F8 and F12, 10% w/v of fructose solution to drink), during 4, 8 and 12 weeks (n = 8/group/period). Urinary L-dopa and dopamine (DA) (HPLC), diuresis and albuminuria were determined. Systolic blood pressure (SBP) (tail cuff) and metabolic parameters were measured. Western blot analysis of renal expression of dopamine 1 receptor (D1R), NFkappa-beta, IL-6, TNF-alpha, TGF-beta1 and nephrin were performed. Results: Fructose overload increased SBP (mmHg, C4: 121 ± 8 vs. F4: 145 ± 1 * ; C8: 130 ± 4 vs. F8: 161 ± 10#; C12: 133 ± 5 vs. F12: 163 ± 4#), which positively correlated (R2 = 0.78; p < 0.002) to urinary L-dopa/DA index (C4: 0.49 ± 0.05 vs. F4: 1.9 ± 0.09#; C8: 0.53 ± 0.06 vs. F8: 2.35 ± 0.1#; C12: 0.54 ± 0.07 vs. F12: 2.57 ± 0.2#). A significant decrease in the D1R expression was related to a significant increase in nFkappa-beta, IL-6, TNF-alpha, TGF-beta1 expression since week 4. Microalbuminuria (C12:13.11 ± 1.4 vs F12:57.6 ± 2.5#) and a decrease in nephrin expression (C12: 1.00 ± 0.10 vs. F12: 0.73 ± 0.05#) were observed only at week 12. ( * p < 0.05, # p < 0.01 vs. C). Conclusions: Fructose overload was associated to an L-dopa/DA index increase and D1R expression decrease since week 4 of treatment. The renal dopaminergic system dysfunction was accompanied by an increase in blood pressure levels and renal expression of inflammatory markers in all experimental periods studied. Alteration of L-dopa/DA index could be an earlier marker of renal dysfunction than the structural damage evidenced by microalbuminuria and decreased nephrin expression in week 12 of fructose treatment.